Study of law-frequency noise in amorphous silicon - Pekcan, İ. Hakan. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1987., 1987)
In this thesis, amorphous silicon films are fabricated and their low-frequency noise properties are investigated over the range of 10 Hz to 4.4 kHz. The ohmic contacted films are produced in two different geometries using the electron gun vacuum-evaporation technique. The noise measurements carried out at low-frequencies show that, 1/f noise is dominant in this frequency region. Effects of d.c. biasing and increasing ambient temperature are also investigated; increasing temperature (> 300 °K ) decreases the low-frequency noise power level. The relationship between the hopping rate and the 1/f noise is verified. It is also shown that, the density of states near the Fermi level can be calculated from 1/f noise measurements. Amorphous silicon films are found to be noisier than the crystalline structure.
Keywords: Amorphous semiconductors.; Silicon crystals.; Thin film devices.; Silicon alloys.